2012
DOI: 10.1080/10894160.2011.557644
|View full text |Cite
|
Sign up to set email alerts
|

Out Lesbians in Nursing: What Would Florence Say?

Abstract: Research and education on lesbian health has increased substantially in quantity and quality in the past 40 years, but little of this work has been produced by nursing scholars. We began our academic nursing careers as out lesbian faculty at the same college of nursing in the late 1980s, where we collaborated on the earliest studies of attitudes about lesbians in the nursing profession. Our paths diverged in the early 1990s, but we shared similar experiences in nursing education that highlight the structural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Furthermore, information about lesbians and prejudice remains insuffi cient, especially in the nursing sector (Randall & Eliason, 2012). The participants of this study may also perceive other contexts as simply more discriminatory, what might constitute a concerning factor given the levels of homophobia found in healthcare contexts (e.g., Campo-Arias et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Furthermore, information about lesbians and prejudice remains insuffi cient, especially in the nursing sector (Randall & Eliason, 2012). The participants of this study may also perceive other contexts as simply more discriminatory, what might constitute a concerning factor given the levels of homophobia found in healthcare contexts (e.g., Campo-Arias et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…More information about this community should be provided during nursing training. The inclusion of information about lesbians in nursing manuals and curricular programs seems to be very important to avoid marginalisation and invisibility of this community (Randall & Eliason, 2012). Therefore, nursing schools should provide general training and education about LGBT issues and more specifi cally about lesbians, in order to prevent prejudice against this group of patients, but also as a way of tackling specifi c health care needs of this group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research that explores the preparedness of nurses and other healthcare providers to care for LGBTQ individuals finds that the majority of students lacked sufficient knowledge to be able to provide care [ [21]. These same researchers also frequently found that faculty and educators also felt ill-equipped to teach LGBTQ content.…”
Section: Providing Care To Lgbtq Individualsmentioning
confidence: 99%